Correct Answer - Option 2 : B = 3A

**Given:**

A = 382 - 326 - 5 × (1/3) of 60 + {32 × (20 - 15)}

B = 6 ÷ 18 × 75 - {(2/3) of 90 - 114 ÷ 3}

**Concept:**

BODMAS Principle:

Solve for:

1) Expressions in the bracket first. Apply BODMAS rule inside the bracket also.

2) Operations 'of' (Multiplication) and 'order' (exponent)

3) Division

4) Multiplication

5) Addition and Subtraction

**Calculation: **

A = 382 - 326 - 5 × (1/3) of 60 + {32 × (20 - 15)}

⇒ 56 - (5 × 20) + (9 × 5)

⇒ 56 - 100 + 45 = 1

∴ A = 1

Now,

B = 6 ÷ 18 × 75 - {(2/3) of 90 - 114 ÷ 3}

⇒ (1/3) × 75 - (60 - 38)

⇒ 25 - 22 = 3

∴ B = 3

Now we have A = 1 and B = 3

∴ B = 3A